Misinterpretation of Genomic Data Matters for Endangered Species Listing: The Sub-specific Status of the Peñasco Least Chipmunk (Neotamias minimus atristriatus) - Hope, Andrew G.; Frey, Jennifer K. (Frontiers in Conservation Science, 2022)
We provide a response to a recently published evaluation of the subspecies status of the Peñasco least chipmunk (Neotamias minimus atristriatus). The work we discuss used exon capture genomic approaches and concluded that their results did not support the distinction of this taxon as a subspecies, with recommendation that it be synonymized with N. m. operarius. We refute the interpretations, conclusions, and taxonomic recommendations of this study, and explain in clearer terms how to interpret genomic analyses for applied management. We identify four broad conceptual issues that led to errant recommendations: (1) interpretation of subspecies and diagnosability, (2) inappropriate use of reciprocal monophyly as a criterion for subspecies, (3) importance of geographic isolation, and (4) error in hypothesis testing and misinterpretation of results. We conclude that the data from this genomic appraisal add to information from prior studies providing strong support for recognition of N. m. atristriatus as a subspecies. Our conclusions have important and immediate implications for the proposed listing of N. m. atristriatus as an endangered species under the U.S. Endangered Species Act.